Structural Relationship of the Lipid A Acyl Groups to Activation of Murine Toll-Like Receptor 4 by Lipopolysaccharides from Pathogenic Strains of Burkholderia mallei, Acinetobacter baumannii, and Pseudomonas aeruginosa - Korneev, Kirill V.; Arbatsky, Nikolay P.; Molinaro, Antonio; Palmigiano, Angelo; Shaikhutdinova, Rima Z.; Shneider, Mikhail M.; Pier, Gerald B.; Kondakova, Anna N.; Sviriaeva, Ekaterina N.; Sturiale, Luisa; Garozzo, Domenico; Kruglov, Andrey A.; et al. (Frontiers in Immunology, 2015)
Toll-like receptor 4 (TLR4) is required for activation of innate immunity upon recognition of lipopolysaccharide (LPS) of Gram-negative bacteria. The ability of TLR4 to respond to a particular LPS species is important since insufficient activation may not prevent bacterial growth while excessive immune reaction may lead to immunopathology associated with sepsis. Here we investigated the biological activity of LPS from Burkholderia mallei that causes glanders, and from the two well-known opportunistic pathogens Acinetobacter baumannii and Pseudomonas aeruginosa (causative agents of nosocomial infections). For each bacterial strain, R-form LPS preparations were purified by hydrophobic chromatography and the chemical structure of lipid A, an LPS structural component, was elucidated by HR-MALDI-TOF mass spectrometry. The biological activity of LPS samples was evaluated by their ability to induce production of proinflammatory cytokines, such as IL-6 and TNF, by bone marrow-derived macrophages (BMDM). Our results demonstrate direct correlation between the biological activity of LPS from these pathogenic bacteria and the extent of their lipid A acylation.